The next grave - Elliot, Kendra (Columbia River, 2024)
Detective Evan Bolton is gutted by his latest investigation. His friend and mentor, retired detective Rod McLeod, has been murdered, his body left in the trunk of a junkyard car. When McLeod's daughter and grandson abruptly vanish, Evan knows it's not a coincidence. Search and rescue canine specialist Rowan Wolff agrees as she and her dog, Thor, track the missing family. The two cases converge in a puzzling twist. Evan discovers that McLeod has been reinvestigating old crimes--solved but not forgotten. Evan takes them on, one by one, and a disturbing suspicion forms that someone in law enforcement has something to hide and would do anything to keep those secrets buried. But Evan and Rowan's time is slipping away. They have to find the killer now. Before someone else disappears. Before someone else dies.